Two new species of Xestia Hübner, 1818 (Lepidoptera, Noctuidae) from Bhutan and China - Gyulai, Péter (Zootaxa, 2017)
Xestia Hübner, 1818 is a diverse and widespread Noctuinae genus, most of the known species occur in the Holarctic and the rest in Africa. Due to the expeditions to the hardly explored area of Asia, new species of Xestia have been recognized and described during the last years (Gyulai et al. 2011, 2013; Gyulai & Ronkay 2016). A German expedition (Ratzel, Hauenstein, M. Falkenberg & Trusch) led to the high altitude region of western Bhutan, collected a series of a rather small Perissandria Warren, 1909—like species, of which the genitalia show, surprisingly, the typical features of Xestia, displaying conspicuous external and genitalia differences, comparing with the Tibetan Xestia lithoplana Hreblay, Ronkay & Plante, 1998. The second new species described here below, has already been under discussion for a long time. The genitalia slide was provided by the late Márton Hreblay, from the author‘s material and suspected by him as Paramathes Boursin, 1954. After the revision of the genus Paramathes (Varga et al 2015), the detailed study led to the recognition that it cannot be a Paramathes, but a hitherto unknown Xestia.  Thus, the description of the two new species appears to be reliable and is presented below.